Species identification and selection to develop agroforestry at Lake Toba Catchment Area (LTCA) - NURHENI WIJAYANTO (Biodiversitas Journal of Biological Diversity, 2011)
Wijayanto N (2011) Species identification and selection to develop agroforestry at Lake Toba Catchment Area (LTCA). Biodiversitas 12: 52-58. In order to improve land productivity surrounding the LTCA, the existing ITTO project tries to establish agroforestry system. The system will be designed to meet consideration of both sides. on one side is to generate the people awareness of the forest and land rehabilitation, and on the other side is to support the poverty reduction. The aims of this research are: species identification and selection to develop agroforestry at LTCA. Data collecting was carried out with: interview, group discussion, field observation, divining manual study, and PRA. The diversity of the available crop kind shows the number of choices to be developed by the farmer. The farmers generally have the economic objective to develop agroforestry, including increase in net income, risk reduction, increase in environmental service, and the wealth and savings accumulation. Various types of agricultural crops, plantations and forest trees were found in LTCA. They can be the basis for building a wide variety of agroforestry systems.Key words: catchment area, agroforestry system, sequential, integrated.